Japan's World Heritage sites - Dougill, John (Tuttle Publishing, 2019)
n Japan's World Heritage Sites, readers are introduced to the temples, gardens, castles and natural wonders for which Japan is so justly renowned all of those now declared to be Unesco World Heritage Sites. Author John Dougill traveled to all the sites and describes each in detail, stating why they were singled out by Unesco, the current number and types of sites, the application process, how the sites have been selected, and how difficult it is to be given the special status of a World Heritage Site. Readers will learn how Japan first became involved with the World Heritage Sites program back in 1993, the importance of these designations, and their popularity in Japan and abroad today, where they are visited by millions of people annually, both Japanese and foreigners.